(untitled) (Czech Journal of International Relations, 2007)
Dionyssis G. Dimitrakopoulos – Argyris G. Passas (eds.): Greece in the European Union. 1st ed. London – New York: Routledge, 2004, 164 stran, ISBN 0-415-25811-1 (signatura knihovny ÚMV 51 860).